WAIVER OF ARTICLE 1245, FORCE MAJEURE IN COVID-19 PANDEMIC - Vera Wheni Setijawati Soemarwi; Merri Lutfiyah Amelia (LPSDI Bina Patria, 2023)
The COVID-19 pandemic that has occurred since the end of 2019 has hit all countries in the world. The impact experienced by every country, including Indonesia, is the decline in the health of its citizens due to infection with the Corona virus, the decline in the economic capacity of the country and its citizens due to the implementation of restrictions on periodic social activities, as well as security in the country's border areas (Abron, 2021). These three impacts were not considered force majeure conditions in the Airmadidi District Court Decision Number 11/Pdt.G.S/2021/PN. Arm (Verdict a-quo). The debtor's inability to pay multipurpose financing installments as a result of imposing restrictions on social and economic activities is not considered a coercive circumstance or a condition beyond the ability of the debtor. This research will examine the a-quo decision by applying the socio-legal studies approach. The purpose of this research is to provide legal certainty in the application of force majeure and default cases.